Leveraging Governmental Auditing for Strategic Decision-Making and Policy Evaluation - Noch, Muh Yamin; Sonjaya, Yaya (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
The purpose of this study is to examine the transformative role of governmental auditing in informing strategic decision-making and policy evaluation within the public sector. Through a systematic literature review, the study investigates the evolution of governmental auditing practices, encompassing financial oversight, compliance assessment, and risk management. Methodologically, this research adopts a qualitative approach, analyzing existing literature to identify trends, challenges, and opportunities in governmental auditing. The findings indicate a paradigm shift towards a holistic auditing framework that integrates financial, environmental, and social dimensions. The discussion highlights the importance of credibility, relevance, and uptake of audit findings in decision-making processes, emphasizing transparency, independence, rigor, and effective communication as critical factors. The implications of the study underscore the need for governmental auditors to embrace strategic and risk-oriented approaches, aligning audit objectives with organizational goals and priorities. This study contributes to the literature by providing insights into the multifaceted nature of governmental auditing and its implications for governance practices